Socioeconomic Status and Risk-Taking Behavior Among Chinese Adolescents: The Mediating Role of Psychological Capital and Self-Control - Jia, Xiaoshan; Zhu, Haidong; Sun, Guiqin; Meng, Huanlei; Zhao, Yuqian (Frontiers in Psychology, 2021)
Risk-taking behavior is particularly widespread during adolescence, and negatively impacts the healthy growth and social adaptation of adolescents. Utilizing problem-behavior theory and the family stress model, the current study examined the relationship between socioeconomic status and adolescents’ risk-taking behavior, as well as the mediating role of psychological capital and self-control. A total of 1156 Chinese adolescent students (Mage=15.51，48% boys) completed a series of questionnaires anonymously. The results showed that: (1) Socioeconomic status was negatively correlated with adolescents’ risk-taking behavior; (2) Both psychological capital and self-control mediated the relationship between socioeconomic status and adolescents’ risk-taking behavior independently; (3) Psychological capital and self-control also mediated the relationship between socioeconomic status and the risk-taking behavior of adolescents sequentially. This study reveals the internal mechanism of risk-taking behavior during adolescence and provides theoretical support and empirical evidence for preventing and reducing such behavior in this age group.